Alterations in the default mode‐salience network circuit provide a potential mechanism supporting negativity bias in depression. (17th August 2021) - Guha, Anika; Yee, Cindy M.; Heller, Wendy; Miller, Gregory A.
Abstract: Aberrant effective connectivity between default mode (DMN) and salience (SAL) networks may support the tendency of depressed individuals to find it difficult to disengage from self‐focused, negatively‐biased thinking and may contribute to the onset and maintenance of depression. Assessment of effective connectivity, which can statistically characterize the direction of influence between regions within neural circuits, may provide new insights into the nature of DMN‐SAL connectivity disruptions in depression. Functional magnetic resonance imaging (fMRI) was collected from 38 individuals with a history of major depression and 50 healthy comparison participants during completion of an emotion‐word Stroop task. Activation within DMN and SAL networks and effective connectivity between DMN and SAL, assessed via Granger causality, were examined. Individuals with a history of depression exhibited greater overall network activation, greater directed connectivity from DMN to SAL, and less directed connectivity from SAL to DMN than healthy comparison participants during negative‐word trials. Among individuals with a history of depression, greater DMN‐to‐SAL connectivity was associated with lower overall network activation and worse task performance during positive‐word trials; this pattern was not observed among healthy participants. Present findings indicate that greater network activation and, specifically, influence of DMN on SAL, support negativity bias among previously depressed individuals. Abstract : Negativity bias in depression refers to abnormal processing of and preferential attention to negative stimuli. The complex and dynamic pattern of disruptions to attentional and emotional processes in depression is consistent with accumulating evidence of dysfunction involving large‐scale neural networks that may contribute to negativity bias in the disorder. This study identifies patterns of causal influences between networks during the processing of negative emotional stimuli that may serve as mechanisms of vulnerability to clinical depression.